A case of retinal ciliary artery obstruction complicated after nonarteritic anterior ischemic optic neuropathy - Huang, Yihong; Huang, Guangqian; Zhu, Xinxing; Peng, Fengxue; Zhang, Yan (BMC ophthalmology, 2025)
Nonarteritic Anterior Ischemic Optic Neuropathy(NAION) results from disease of the small vessels supplying the anterior portion of the optic nerve, its exact cause remains unknown. The retinal Ciliary Artery Obstruction (CrAO), may be identified in one-third of normal eyes. This congenital vascular variant arises from the peripapillary choroid or directly from one of the short posterior ciliary arteries. Some literature had indicated a potential correlation between the occurrences of NAION and CrAO. A 54-year-old male presented with a one-week history of visual field occlusion in his right eye.Fundus examinations revealed marked disc swelling and flame-shaped hemorrhages in the superior nerve fiber layer in the right eye, along with a small, crowded optic disc of left eye. He was diagnosed with NAION based on clinical and funduscopic fundings. Two days after the initial presentation, the patient developed CrAO in the affected eye, accompanied by worsening retinal edema and increased flame hemorrhage intensify. The patient was treated with intravenous methylprednisolone 500 mg/day for three days, following by oral methylprednisolone at 1 mg/kg/day for one week. At the six-month follow-up, visual acuity in the right eye remained unchanged, and the optic disk was pale. We reported a case of complications of CrAO arising after NAION which caused the mechanical compression on the ciliary artery circulation.